2014
DOI: 10.7314/apjcp.2014.15.1.419
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Lymphadenopathy in Kashmir Valley: A Clinicopathological Study

Abstract: Background: Lymphadenopathy is a common presentation in both benign and malignant diseases which need to be diagnosed without delay. Fine needle aspiration cytology (FNAC) helps us diagnose a disease and follow its course, including the response to therapy. Aim: This study aimed to analyze the clinicopathological features of metastatic lymphadenopathy and the diagnostic utility of FNAC in our setting. Materials and Methods: This two-year prospective study included all the patients with metastatic lymphadenopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…FNAC is an important tool for metastatic workup, especially in cases of breast carcinoma and head and neck squamous cell carcinoma. A study evaluating metastatic lymphadenopathy by FNAC reported that the supraclavicular lymph node was the most common site of metastatic lymphadenopathy and squamous cell carcinoma was the most common type of metastatic carcinoma [9]. In our study, 19% of lymphadenopathy cases had a cytomorphological diagnosis of metastatic carcinoma, and a significant association of this diagnosis was noted with older age.…”
Section: Discussionsupporting
confidence: 56%
“…FNAC is an important tool for metastatic workup, especially in cases of breast carcinoma and head and neck squamous cell carcinoma. A study evaluating metastatic lymphadenopathy by FNAC reported that the supraclavicular lymph node was the most common site of metastatic lymphadenopathy and squamous cell carcinoma was the most common type of metastatic carcinoma [9]. In our study, 19% of lymphadenopathy cases had a cytomorphological diagnosis of metastatic carcinoma, and a significant association of this diagnosis was noted with older age.…”
Section: Discussionsupporting
confidence: 56%
“…reported 50% metastatic lymph nodes, followed up by 30% subsequent surgical excisions; in our metastatic series, we found 68% surgical excisions justified for the management of the primary cancers. Based on our evidence, the most common metastatic tumour is represented by thyroid carcinoma, whereas Qadri et al . reported lung, oesophagus, stomach and breast as the most common primary malignancies.…”
Section: Discussionmentioning
confidence: 75%
“…Several authors have recognized the central role of this cytological approach in the diagnostic evaluation of reactive lymphoid hyperplasia, infectious diseases and granulomatous lymphadenitis, strongly encouraged by the invaluable cost‐effectiveness of this technique . Moreover, not only is it a painstaking additional parameter in patients with a known primary malignancy, it may also represent the first diagnostic detection of an unknown primary cancer . In addition, all of these advantages of FNAC have been enhanced by the excellent results obtained in the diagnosis and staging of lesions through the application of the minimally invasive diagnostic approach of endoscopic ultrasound‐guided (EUS) biopsy, especially in patients with metastatic or locally advanced tumours …”
Section: Introductionmentioning
confidence: 99%
“…Enlarged cervical lymph nodes are a common finding on physical examination in the pediatric population (Rajasekaran and Krakovitz,Hussainy 1 , Ahmed Safar Alhujaily 2 more common in this age group (Jamal et al, 2014); in contrast to the other extreme of age exhibiting metastasis from nearby or distant malignancies (Qadri et al, 2012;Lad et al, 2014).…”
Section: Introductionmentioning
confidence: 99%